PENGARUH LEVERAGE, LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN MODAL KERJA SEBAGAI VARIABEL MEDIASI - Fangestu, Steven; Liesani, Valencia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study examines the effect of leverage, liquidity, and profitability on dividend policy, with working capital as a mediating variable, using data from manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2023. A total of 73 companies were selected from 318 using purposive sampling. The study employed secondary data obtained from published annual financial reports. Analysis was conducted using the two-stage approach to test both the direct and indirect effects of the independent variables on dividend policy, as well as to assess the mediating role of working capital. The findings indicate that leverage, liquidity, and profitability do not have a significant direct impact on dividend policy. Furthermore, working capital does not mediate the relationship between the independent variables and dividend policy. These results suggest that dividend distribution decisions in the observed companies may be influenced by other financial or strategic considerations beyond the variables examined in this study.